Yellow Means Caution: Correlations Between Liver Injury and Mortality with the Use of VA-ECMO. Issue 8 (November 2019) - Masha, Luke; Peerbhai, Shareez; Boone, David; Shobayo, Fisayomi; Ghotra, Aman; Akkanti, Bindu; Zhao, Yelin; Banjac, Igor; Gregoric, Igor D.; Kar, Biswajit
Abstract : Abnormalities in markers of liver injury after venoarterial extracorporeal membrane oxygenation (VA-ECMO) initiation are of unclear distribution and clinical significance. This study included all consecutive adult patients from a single institution who underwent VA-ECMO cannulation between May 2012 and September 2016 and had liver function panels drawn during their admission (n = 223). Data points include: age, sex, body mass index, diagnosis, duration of ECMO cannulation, duration of hospitalization, pre-ECMO cardiac arrest, central nervous system (CNS) injury, the presence of chronic kidney disease or acute renal failure, renal replacement therapy utilization, lactate levels, duration of pre-ECMO intubation, admission and peak bilirubin/aspartate aminotransferase (AST)/alanine aminotransferase (ALT)/alkaline phosphatase (ALP) levels, and time to peak bilirubin/AST/ALT/ALP in relation to cannulation. Multivariate Poisson regression analyses were performed to determine associations with mortality. In-hospital mortality was 66%. Serum bilirubin elevation appeared to significantly correlate continuously with mortality. Other markers of liver injury were not significant in final multivariate models. As a univariate factor, no patient survived with a total serum bilirubin greater than 30 mg/dl, and specificity for 90% mortality was crossed at 11 mg/dl. Mortality was also significantly associated with the presence of CNS injury and elevation of lactic acid levels. Postcannulation liver injury is significantly associated with increased mortality and total serum bilirubin appears to be a biomarker of considerable clinical significance.